2021
DOI: 10.1126/sciadv.abc6266
|View full text |Cite
|
Sign up to set email alerts
|

DEAD-box helicases modulate dicing body formation in Arabidopsis

Abstract: Eukaryotic cells contain numerous membraneless organelles that are made from liquid droplets of proteins and nucleic acids and that provide spatiotemporal control of various cellular processes. However, the molecular mechanisms underlying the formation and rapid stress-induced alterations of these organelles are relatively uncharacterized. Here, we investigated the roles of DEAD-box helicases in the formation and alteration of membraneless nuclear dicing bodies (D-bodies) in Arabidopsis thaliana. We uncovered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 78 publications
0
30
0
Order By: Relevance
“…Finally, in M. polymoprha we identified Serrate Associated Protein 1 (Mp SEAP1 ) gene which encodes an ortholog of A. thaliana SEAP1 protein. In Arabidopsis SEAP1 interacts with SE and affects the splicing and early biogenesis stages of a set of miRNAs ( M. Li et al , 2021 ).…”
Section: Higher Plant Mirna Biogenesis Proteins Are Encoded Within Th...mentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, in M. polymoprha we identified Serrate Associated Protein 1 (Mp SEAP1 ) gene which encodes an ortholog of A. thaliana SEAP1 protein. In Arabidopsis SEAP1 interacts with SE and affects the splicing and early biogenesis stages of a set of miRNAs ( M. Li et al , 2021 ).…”
Section: Higher Plant Mirna Biogenesis Proteins Are Encoded Within Th...mentioning
confidence: 99%
“…For instance, genes encoding Small 1 (SMA1) and RNA helicase 8 (RH8) have been identified as Mp SMA1 and Mp RH8 within the M. polymorpha genome. According to Q. Li et al (2021) , Arabidopsis RH8 (together with RH6 and RH12) controls the formation of dicing-bodies (D-bodies) by interacting with the SE protein ( Li et al , 2018 ). However, we did not identify RH6 and RH12 in the M. polymorpha genome.…”
Section: Higher Plant Mirna Biogenesis Proteins Are Encoded Within Th...mentioning
confidence: 99%
“…SE-mediated phase separation is necessary for the formation of D-bodies, in which accurate and efficient miRNA processing occurs (Xie et al, 2021). A recent study also reported that several RNA helicase RH6/8/12 interact with SE and promote the phase separation and the formation of D-bodies (Li Q. et al, 2021).…”
Section: Regulation Of Microrna Processingmentioning
confidence: 99%
“…AtRH27, a DEAD-box RNA helicase in Arabidopsis , has been shown to interact with the biogenesis components of miRNAs (microRNAs) like RNA binding proteins (DAWDLE, HYPONASTIC LEAVES 1 and SERRATE) and regulates miRNA biogenesis 9 . In a recent study which bolsters the association between miRNAs and DEAD-box helicases, it was reported that the DEAD-box helicases modulate the formation of nuclear organelles, the dicing bodies (D bodies) in Arabidopsis , a site where miRNAs are processed 10 .…”
Section: Introductionmentioning
confidence: 99%